2016
DOI: 10.5812/numonthly.40409
|View full text |Cite
|
Sign up to set email alerts
|

Local Administration of Tranexamic Acid During Prostatectomy Surgery: Effects on Reducing the Amount of Bleeding

Abstract: BackgroundOne of the issues in prostatectomy surgery is bleeding. Although tranexamic acid (TRA) is an antifibrinolytic agent for reducing bleeding, controversies surround its use.ObjectivesIn this study, the effect of local administration of TRA on reducing bleeding during prostatectomy surgery was evaluated.MethodsA total of 186 patients who underwent prostatectomy surgery were assessed in this clinical trial study. Patients were divided randomly into two groups. After prostate removal, TRA (500 mg TRA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
5
11
0
1
Order By: Relevance
“…Additionally, there was a significant difference between the two groups’ serum HCT at both 4- and 24-h postoperatively. The Pourfakhr et al [ 9 ] study agrees with our present study, as they reported that a local administration of TXA significantly reduced postoperative HCT loss ( P = 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, there was a significant difference between the two groups’ serum HCT at both 4- and 24-h postoperatively. The Pourfakhr et al [ 9 ] study agrees with our present study, as they reported that a local administration of TXA significantly reduced postoperative HCT loss ( P = 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Topical action of tranexamic acid has shown favorable results in reducing blood loss in total knee arthroplasty and prostatectomy. 16,17 However, no study has been made for its use in tumescent anesthesia. Previously, standard tumescent anesthesia was used, and some amount of blood loss was encountered which needed electrocauterization.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence of the bene cial use of tranexamic acid in cardiac surgery, neurosurgery, traumatology, and orthopedics has led to the renewal of this idea (18)(19)(20). However, newer urological papers continue to produce ambiguous results, from clearly negative (21) to con rmation of the positive effect (22)(23)(24)(25), including a recent meta-analysis (26). Therefore, this trial was conducted in order to clarify this issue.…”
Section: Introductionmentioning
confidence: 99%